Mg-doped VO2@ZrO2 core-shell nanoflakes for thermochromic smart windows with enhanced performance - Wen, Zuohao (2021)
The VO2-based smart windows can dynamically and reversibly adjust the indoor solar irradiation to reduce the energy consumption for building glasses. The paper reports the first successful preparation of Mg-doped VO2@ZrO2 core-shell nanocrystals with promoted thermochromic performance as well as tunable appearance and wettability. To our knowledge, the achieved combination of Tlum of 52.4% and ∆Tsol of 7.1% is comparable to the best-reported results of VO2-based core-shell rod structures. The thickness of ZrO2 shell is tunable between 3-14 nm, resulting in a slightly hydrophobic surface and a slight color change toward blue-green and brighter produced films. The preparation method based on hydrothermal and UV-curing methods is facile. The work may inspire future development of VO2 synthesis, their structure-property, and the application the thermochromic films for energy-saving purposes in buildings or automobiles.